KAPABILITAS KERJA PEGAWAI, PROSEDUR KERJA, BUDAYA KERJA DAN KUALITAS PELAYANAN PUBLIK - Junaidi ' (Universitas Riau, 2017)
Abstract: Employee Capability, Work Procedures, Work Culture and Quality of PublicServices. This research study aims to determine and analyze the relationship between the variablesof employee capabilities, work procedures, work culture with the quality of public services.Design research using quantitative research methods. The population is customers as much as6204 and a sample of 100 people were taken by using the formula slovin. Data collection techniquesusing questionnaires and documentation. The analysis showed that the capability of employee,job procedures and work culture has a tendency to relatively weak positive relationshipwith the variable quality of public services. Thus the hypothesis statement “there is a positiverelationship between employee capabilities, work procedures and work culture, quality of publicservices at the Regional Water Company (PDAM) Indragiri Hulu” either individually or simultaneouslyacceptable.